Effect of Bypass Fat and Fibrolytic Enzymes on Milk Yield and Milk Composition of Surti Buffaloes - Movaliya, Jignesh. K.; Kumar, Brishketu; Rao, Krishna S.; Patel, Vipul. R.; Raval, Ajay P. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The investigation was planned to study the effect of bypass fat @ 1 and 2 % of DMI with exogenous fibrolytic enzymes (EFE) supplementation for 150 days on nutrients utilization and milk production in lactating buffaloes. Recently calved twenty-four lactating buffaloes were assigned to four different treatment groups (n=6 animals in each) that included control, EFE (8 g mixture containing an equal proportion of cellulase minimum 100000 IU/g and xylanase minimum 50000 IU/kg) alone, and EFE with bypass fat @ 1 % and 2 % of DMI, respectively. The digestibility trial of seven days was conducted at the end of the experiment. Any treatment did not influence feed, dry matter and nutrients intake in buffalo. EFE supplementation alone or with 1% bypass fat had significantly (p <0.05) improved digestibility of organic matter, crude protein, ether extract, detergent fiber, and cellulose. The milk production of buffaloes was significantly (p <0.05) higher in groups supplemented with EFE and EFE with 1% bypass fat. Milk compositions did not alter significantly with these supplementations. The study concluded that bypass fat supplementation @ 1% of DMI with 8 g exogenous fibrolytic enzymes mixture mixture (containing equal proportion of cellulase minimum 100000 IU/g and xylanase minimum 50000 IU/kg) improved digestibility of nutrients, which was reflected by higher milk production in Surti buffaloes.